Attitude of students towards information access issues: The case of International Islamic University Malaysia - Mohamud, Ibrahim Kalif; M.Khedher, Akram M. Zeki; Saidin, Aznan Zuhid (Medwell Publishing, 2016)
Among the many challenges of the information age is the information access issues. The vast array of developed technology devices have resulted in emerging many ethical issues that needs to be addressed. The continuous rapid development of ICT will continue to raise new ethical issues and students are likely to have little understanding of the ethical issues associated with using ICT. This study explores the attitude held by the students of International Islamic University Malaysia' (HUM) towards information access issues. It also investigates the differences of the students' individual characteristics of gender, age, marital status, level of study and computer usage with regard to their attitude towards information access issues. Using an adapted instrument, 219 survey questionnaires were analyzed after collecting them from the undergraduate and graduate students of HUM in Gombak campus. Students were found to be sensitive to the unethicality of information access that is unauthorized access to computing and information resources for personal gain. There were no significant differences of the students' individuals' characteristics of gender, age and marital status with regard to their attitude towards information ethics issues of access. However, level of study and the frequency of computer usage showed the existence of significant differences of the students' attitude towards information access. It is suggested that Revised and updated ethics education courses integrated in the university's curricula can help students develop an ethical responsibility and a proper attitude towards information ethics issues